Development of Viterbi decoder in VHDL - Liu, Jun. (2008)
This reprt briefly introduces the theory of Viterbi algorithm for both hard decision and soft decision decoding and mainly focuses on the design and implementation of the soft decision Viterbi decoder by using VHDL, one of the most popular register transfer level language for the hardware design.